PENGARUH VARIASI UMPAN AROMA TERHADAP JUMLAH LALAT YANG TERPERANGKAP DALAM PERANGKAP WARNA KUNING (Studi di Kandang Sapi Dusun Tegalsari Desa Sidomukti Kecamatan Bandungan Kabupaten Semarang) - Dewi Mustikawati; Martini Martini; Mochamad Hadi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Some species of the fly is a vector borne diseases that contribute to public health problems. A fly can carry 65 million micro-organisms, it is not surprising if many people sick because their food was contaminated by the flies. Therefore, it is necessary to study the methods of control are effective and safe for the environment by using variations of flavor baits (durian, jackfruit, mango, frambozen, and pineapple).Research was aimed to analyze the effect of baits flavour variation to the number of flies caught in a yellow trap. The design study is Pseudo Experiment with design Post Test Only Control Group Design. Research was conducted in a cowshed, Hamlet Tegalsari, Village Sidomukti, District Bandungan, Semarang for 2 days. The experiment was repeated 5 times with the same time of day.The results showed the number of flies caught in a trap without bait is 4, trap with pineapple bait is 13.8, trap with jackfruit bait is 14.6, trap with durian bait is 47.2, trap with mango and frambozen bait is 19.8. The species of flies was trapped is 603 tail Fannia spp and 2 tail Stomoxys calcitrans sp. Data was analyzed by Kruskal Wallis test at the significance level α = 0.05. Results of calculation by Man Whitney test is there are different variations of flavour baits to the number of flies trapped. The order of variation from the lowest to the highest are control, pineapple, jackfruit, mango, frambozen, and durian.